Impact of Discipline-Based vs. Interdisciplinary Orthodontic Courses on Dental Students' Performance - (:unkn) unknown (AMER DENTAL EDUCATION ASSOC-ADEA, 2019)
The aim of this longitudinal study was to assess the effect on dental students' grades of participating in a third-year course taught in orthodontics alone versus an interdisciplinary course taught with orthodontics and pediatric dentistry combined. In the five-year dental curriculum at Yeditepe University in Istabul, Turkey, the third-year orthodontic course was taught as a single discipline until 2010, when the course was redesigned as an interdisciplinary course in orthodontics and pediatric dentistry. This retrospective study analyzed all 540 students' grades in orthodontic courses in the third, fourth, and fifth years from 2003-04 to 2014-15 to determine the impact of the third-year course design on students' performance. Students were divided into two cohorts: group A (which experienced the single discipline course, 2003-04 to 2009-10; 181 female, 117 male) and group B (which experienced the combined course, 2010-11 to 2014-15; 152 female, 90 male). In both groups, significant differences were found for the third-, fourth-, and fifth-year orthodontic grades (p<0.05). The grades of the third-year and fifth-year students in 2014-15 were significantly higher than in 2010-11 (p<0.05) in group B. Intergroup comparison showed that the third- and fifth-year grades were significantly higher in group B than in group A (p<0.05). These results suggest that the interdisciplinary delivery of basic knowledge in the third year had facilitated the learning process and deep learning in the more advanced orthodontic courses in the fifth year.
Keywords: dental education; orthodontics; teaching methods; multidisciplinary learning; LEARNING STYLE PREFERENCES; SAUDI-ARABIA; EDUCATION; GENDER; UNIVERSITY; RIYADH